Perceptions of Grade 12 Students Regarding Physical Literacy - M. Fais Rhamadana; Rizki Apriliyanto; Topo Yono (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to investigate the perceptions of 12th-grade students regarding physical literacy, a multidimensional construct that includes motivation, self-confidence, physical competence, and the knowledge required for lifelong engagement in physical activity. Physical literacy plays a crucial role in promoting active and healthy lifestyles, especially during adolescence—a critical period for developing lifelong health behaviors. Employing a quantitative descriptive design, this study involved 83 students from SMA Negeri Kalisat, Jember, who completed the Indonesian-adapted version of the Perceived Physical Literacy Instrument (PPLI). The instrument consists of 9 Likert-scale items assessing various components of physical literacy. Results revealed that 41.5% of students strongly agreed and 29.7% agreed with the physical literacy indicators, suggesting a generally positive perception. However, a significant number of students expressed uncertainty or disagreement on certain items, particularly related to social skills and self-management. These findings underline the importance of integrating physical literacy into school curricula and physical education programs. Strengthening students’ understanding and awareness of physical literacy can enhance their readiness to engage in lifelong physical activity, improve physical and mental health, and support national efforts toward youth health development.